Taxation of Urban Land and Buildings - Planning Commission (Planning Commission, Government of India, 1970)
The documents “Taxation of Urban Land and Buildings” by B. Nanjundaiah and the summary of urban housing and property development strategies provide a comprehensive overview of India’s urban fiscal and housing policies. Property taxation, a critical revenue source for local bodies contributing nearly half of local tax revenues, suffers from inefficient management, inconsistent assessment practices, and widespread evasion, often due to reliance on annual rental values and lack of trained valuation professionals. Comparative international experiences—including unimproved value taxation in Australia, New Zealand, and Jamaica, graded taxation experiments in Pittsburgh and Hawaii, and systematic property valuation in Halifax, Canada—highlight potential lessons for India, emphasizing the need for centralized valuation agencies and reforms in assessment and collection systems. Concurrently, the Delhi Development Authority’s initiatives in urban housing demonstrate practical strategies to provide affordable housing for low-income groups, including the construction of small tenements, financial subsidies, structured repayment schemes, and the regulation of land acquisition to prevent speculation. Programs such as the Jhuggi-Jhompuri Removal Scheme, lottery-based funding, betterment charges, and compulsory land acquisition underscore the integration of fiscal mechanisms with urban planning objectives. Together, these analyses emphasize the interconnection between efficient property taxation, equitable land management, and strategic housing development, highlighting the potential for India to enhance local revenue generation, promote optimal land use, mitigate urban housing shortages, and foster inclusive urban growth through well-coordinated fiscal, regulatory, and development measures.
Planning Commission Perspective Planning Division December 1970
Keywords: Property Tax; Urban Land; Buildings; Local Revenue; Valuation; Housing Development; Low-Income Groups; Land Acquisition; Subsidy; Regulatory Framework; Betterment Charges; Urban Planning